PROSES BERPIKIR SISWA KELAS VII SMP NEGERI 2 SEMEN KEDIRI BERDASARKAN TAHAP PROSES BERPIKIR SOLSO DALAM MEMECAHKAN MASALAH MATEMATIKA DITINJAU DARI ADVERSITY QUOTIENT (AQ) - Anis Hanafiah; Riyadi Riyadi; Imam Sujadi (Journal of Mathematics and Mathematics Education, 2016)
Abstract: The purposes of the research were to describe (1) Thinking process of climber students grade VII SMPN 2 Semen in problem solving of mathematics. (2) Thinking process of camper students grade VII SMPN 2 Semen in problem solving of mathematics (3) Thinking process of quitter students grade VII SMPN 2 Semen in problem solving of mathematics. The thinking process in this research uses steps of Solso thinking, forming concept, logically, and taking decision. This research is qualitative descriptive research. The subjects in this research are taken by purposive sampling. The subjects of this research are 3 students from grade VII SMPN 2 Semen, they are 1 student of climber type, 1 student of campers type, and 1 student of quitters type. The data collection of this research uses polling and questionaire technic based on duties that is done for comparison material. The legality of data used in this research is triangulation time and using reference sufficience. The technic of data analysis used is Miles and Huberman concept, these are data reduction, giving data and getting conclution. The results of this research show that (1) the thinking process of climber students, in problem solving of mathematics on steps: (a) understanding the problem that have done: (i) forming concept, (ii) thinking logically, (iii) taking decision; (b) arranging the plan for problem solving by: (i) forming concept, (ii) thinking logically, (iii) taking decision. (c) doing the plan of problem solving by: (i) forming concept, (ii) thinking logically, (iii) taking decision. (d) recheck the result by: (i) forming concept, (ii) thinking logically, (iii) taking decision; (2) The thinking process of camper students in problem solving of mathematics on steps: (a) understanding the problem by: (i) forming concept, (ii) thinking logically, (iii) taking decision. (b) arranging the plan for problem solving by: (i) forming concept, (ii) thinking logically, (iii) not taking decision. (c) doing the plan for problem solving, by (i) forming concept, (ii) thinking logically, (iii) taking decision. (d) recheck the result by: (i) forming concept, (ii) thinking logically, (iii) not taking decision. (3) The thinking process of quitter students in problem solving of mathematics on steps: (a) understanding the problem by, (i) forming concept, (ii) not thinking logically, (iii) can’t take decision. (b) planning for problem soving: (i) not forming concept, (ii) thinking logically, (iii) can’t take decision, (c) can’t run for the probem solving. (d) not rechecking the problem solving.Keywords: thinking process, problem solving, Adversity Quotient (AQ)